Ian Prior and epidemiology in New Zealand. - Pearce N (B M J PUBLISHING GROUP, 2009)
Ian Prior was born in Masterton, New Zealand, in 1923, and died in Wellington, New Zealand, in 2009. In 1959 Ian became the Director of the Medical Unit at Wellington Hospital, and in the early 1960s he established the Epidemiology Unit. Without doubt he is the founder of epidemiology in New Zealand, and has also had a major influence in Australia and further afield. I was delighted to be invited to write this piece about Ian for the Journal of Epidemiology and Community Health, not as an obituary but as an essay on an epidemiologist who inspired many of us in New Zealand, and whose example will continue to inspire many around the world. Ian Prior's work represents not only an important historical legacy but also an important guide to the future of epidemiology. This includes his work on the effects of social and environmental changes and the wider social context on individual "lifestyle", his willingness to work collaboratively with researchers from other disciplines including social scientists, his insistence on seeing quantitative biomedical phenomena (such as blood pressure) in the wider social context, and perhaps most of all his insistence that epidemiologists cannot hide from the wider realities of the world in which they live.
Essay
Keywords: Ian Prior; Epidemiology; New Zealand; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321202 Epidemiology